Scaling DNA data storage with nanoscale electrode wells - Nguyen, Bichlien; Takahashi, Christopher; Gupta, Gagan; Smith, Jake; Rouse, Richard; Berndt, Paul; Yekhanin, Sergey; Ward, David; Ang, Siena; Garvan , Patrick; Parker, Hsing-Yeh; Carlson, Rob; et al. (Science Advances, 2021)
Synthetic DNA is an attractive medium for long-term data storage because of its density, ease of copying, sustainability, and longevity. Recent advances have focused on the development of new encoding algorithms, automation, preservation, and sequencing technologies. Despite progress in these areas, the most challenging hurdle in deployment of DNA data storage remains the write throughput, which limits data storage capacity. We have developed the first nanoscale DNA storage writer, which we expect to scale DNA write density to 25 × 106 sequences per square centimeter, three orders of magnitude improvement over existing DNA synthesis arrays. We show confinement of DNA synthesis to an area under 1 square micrometer, parallelized over millions of nanoelectrode wells and then successfully write and decode a message in DNA. DNA synthesis on this scale will enable write throughputs to reach megabytes per second and is a key enabler to a practical DNA data storage system.